2010
DOI: 10.1002/chem.201002542
|View full text |Cite
|
Sign up to set email alerts
|

One‐, Two‐ and Three‐Periodic Metal–Organic Rotaxane Frameworks (MORFs): Linking Cationic Transition‐Metal Nodes with an Anionic Rotaxane Ligand

Abstract: A new singly charged pyridinium axle was prepared and combined with disulfonated dibenzo[24]crown-8 ether to form a [2]pseudorotaxane. The reaction of this new, anionic ligand with Zn(II) ions, under various crystallization conditions, resulted in the formation of three metal-organic rotaxane framework (MORF) solids; a one-periodic ML coordination polymer and two, two-periodic ML(2) square grid frameworks. The layers of square grids can be pillared to create full three-periodic MORF structures, which have comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 61 publications
0
26
0
Order By: Relevance
“…As a typical O‐donor anion, the coordination capacity of the sulfate ion is comparable to other O‐donor ligands, such as the carboxylate group. Loeb et al . reported previously a similar phenomenon of controlling the structure of Zn‐based MORFs by the sulfate ion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a typical O‐donor anion, the coordination capacity of the sulfate ion is comparable to other O‐donor ligands, such as the carboxylate group. Loeb et al . reported previously a similar phenomenon of controlling the structure of Zn‐based MORFs by the sulfate ion.…”
Section: Resultsmentioning
confidence: 99%
“…As atypical O-donor anion,t he coordinationc apacity of the sulfate ion is comparablet oo ther O-donorl igands, such as the carboxylate group. Loeb et al [23] reported previously as imilar phenomenon of controlling the structure of Zn-based MORFs by the sulfatei on. Our group recently afforded another two cases involvingt he uranyl center, [17a, b] which demonstrated its moderate binding affinity to the uranyl ion.…”
Section: Supramolecular Interaction In Compound 1asw Ell As Its Possimentioning
confidence: 89%
“…In addition, [2]rotaxanes, wherein the dumbbell components function as struts in the frameworks, have also been incorporated4 into MOFs. While this strategy has been applied4af to the preparation of a number of 2D and 3D frameworks from [2]pseudorotaxanate subunits, it remains a challenge to locate switchable rotaxanes and catenanes inside extended frameworks. Metal‐containing MIMs—particularly those based on the well‐known5 copper(I)‐templated systems—offer the opportunity to locate switches within MOFs.…”
Section: Methodsmentioning
confidence: 99%
“…Following Scheme 1, the cross-coupling reaction between 2-(4-bromophenyl)ethanol and pyridin-4-ylboronic acid was performed on the basis of a procedure reported in the literature [28] by means of Pd(PPh 3 ) 4 as catalyst. The presence of the pyridyl group gave us the opportunity to separate the product 1 from N,N-dimethylformamide (DMF) by precipitating it as hydrochloride salt, avoiding the use of column chromatography and still guaranteeing good yield and optimal purity as detectable with GC-MS and 1 H NMR analyses.…”
Section: Synthesis Of the Tripodal Ligand H 3 Phppymentioning
confidence: 99%
“…This compound was obtained with a modification of a published procedure [28], especially in the final purification step. 2-(4-bromophenyl)ethanol (1.00 g, 4.97 mmol), pyridin-4-ylboronic acid (0.552 g, 4.49 mmol), and Na 2 CO 3 (0.526 g, 4.97 mmol) were introduced in a Schlenk tube under Ar.…”
Section: Synthesis Of 2-(4-(pyridin-4-yl)phenyl)ethanol (1)mentioning
confidence: 99%